2022
DOI: 10.3390/jcm11092574
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic Is Associated with Reduced Survival after Pancreatic Ductal Adenocarcinoma Diagnosis: A Single-Centre Retrospective Analysis

Abstract: The COVID-19 pandemic has hugely disrupted healthcare provision, including oncology services. To evaluate the effects of the pandemic on referral routes leading to diagnosis, treatments, and prognosis in patients with pancreatic ductal adenocarcinoma, we performed a retrospective cohort study at a single tertiary centre in the UK. The patients were identified from the weekly hepatopancreatobiliary multidisciplinary team meetings between February 2018 and March 2021. The demographic, referral, and treatment dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…In real terms, this represented a 4-month reduction in median survival. 3 Our findings are validated by a North American study, which found an increased proportion of patients presenting at later stages and a reduction of 2 months in overall survival in those diagnosed with metastatic PDAC during the pandemic compared with before the pandemic. 4 Several other studies have demonstrated the negative effects of COVID-19 on PDAC diagnosis and management.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…In real terms, this represented a 4-month reduction in median survival. 3 Our findings are validated by a North American study, which found an increased proportion of patients presenting at later stages and a reduction of 2 months in overall survival in those diagnosed with metastatic PDAC during the pandemic compared with before the pandemic. 4 Several other studies have demonstrated the negative effects of COVID-19 on PDAC diagnosis and management.…”
supporting
confidence: 77%
“…We recently published results from our British single-center study, suggesting a halving of median survival for PDAC patients diagnosed during the pandemic compared to a comparable pre-pandemic cohort. In real terms, this represented a 4-month reduction in median survival 3. Our findings are validated by a North American study, which found an increased proportion of patients presenting at later stages and a reduction of 2 months in overall survival in those diagnosed with metastatic PDAC during the pandemic compared with before the pandemic 4…”
supporting
confidence: 76%
See 2 more Smart Citations
“…However, continuous follow-ups should be processed to further observe in a long term. Some studies proposed that the COVID-19 could impair the prognoses of pancreatic cancer patients, 21,22 which probably resulted from the impaired cancer screening, diagnosis, and care. 23 The vaccination was not discovered associated with the OS of PAC patients.…”
Section: Discussionmentioning
confidence: 99%